Inclusive Marketing as a Strategic Tool for Company’s Development in a Socially Oriented Economy - Liulchak, Zoreslava; Ostapenko, Ihor; Boiko, Olha; Kanishchenko, Olena; Vlasenko, Yurii (International Review of Management and Marketing, 2025)
The objective of this study was to evaluate the influence of brand inclusivity perception indicators on a company’s financial performance. Employing correlation, regression, and trend analysis methodologies, the research unveiled that various facets of inclusion manifest in a company’s financial outcomes in distinct manners. This phenomenon can be attributed to the impact of multiple stakeholder groups, namely investors, analysts, and consumers. Notably, a critical determinant affecting Market Capitalization is the engagement of ESG investors, who prioritize companies’ social initiatives, particularly the perception of the LGBT+ community. The regression coefficient for this indicator is 4.6458. Overall, inclusivity in marketing significantly influences both Revenue and Earnings by enhancing customer loyalty, with regression coefficients of 0.3485 and 0.0393, respectively. Furthermore, Revenue, influenced by the perception of brand authenticity, exhibits a regression coefficient of 0.1207. Additionally, perceptions of racial diversity positively affect the P/E ratio, reflected by a regression coefficient of 2.1058, thereby bolstering market confidence. The findings of this study can serve as a valuable resource for companies, enabling them to devise inclusive marketing strategies that align with their objectives and mission.